FITOKIMIA DAN SKRINING AWAL METODE BIOTEKNOLOGI FERMENTASI KOMBUCHA BUNGA TELANG (Clitoria ternatea L) SEBAGAI BAHAN AKTIF SABUN CUCI TANGAN PROBIOTIK - Nurullah Asep Abdilah; Firman Rezaldi; Fernanda Desmak Pertiwi; M. Fariz Fadillah (LPPM Akafarma Sunan Giri Ponorogo, 2022)
Telang flower kombucha fermentation has antibacterial, antioxidant, and anticancer properties so that it has the potential to make probiotic hand soap preparations. Telang flower kombucha fermentation biotechnology as the active ingredient. The work procedure carried out is phytochemical screening and making hand soap preparations. The results showed that the fermented kombucha solution of telang flower contained secondary metabolites from the alkaloid, flavonoid, and saponin groups. Soap preparations were seen prominently on the soap base which was added with fermented kombucha solution of telang flower which indicated the presence of stable anthocyanin content. Telang flower kombucha has the potential to be used as a probiotic hand soap preparation, but it is necessary to evaluate the physical preparation and the antibacterial activity of both gram-positive and gram-negative pathogens. Keywword : Probiotics, antimicrobials, butterfly pea